Image dehazing method based on haze-line and color attenuation prior - Miao LIAO; Yan LU; Jin ZHANG; Yuqian ZHAO; Shuanhu DI (Tongxin xuebao)
To solve the problems caused by the existing image dehazing methods, such as color over-saturation, detail loss, and artifacts, a dehazing method was proposed based on haze-line and color attenuation prior.Firstly, haze-line prior and Hough vote were used to estimate the atmospheric light.Then, a nonlinear model on scene depth was constructed according to color attenuation prior theory to achieve transmission accurately.Finally, the haze was removed from the image by inversely solving the atmospheric scattering model, so as to obtain the dehazed image with rich details.The proposed method was tested on public RESIDE dataset in comparison with many existing methods.Experimental results show that the proposed method can effectively remove the haze from image and obtain a clear and natural dehazed image, which has higher time and space efficiency than other methods.